MAKSIMALISASI KEUNTUNGAN USAHA ROTI DAN BROWNIS PADA INDUSTRI âSYARIAH BAKERYâ DI KELURAHAN TANAMODINDI KECAMATAN PALU SELATAN KOTA PALU - Lantose, Hadayani, Abdul Muis, Lianti S. (AGROTEKBIS, 2016)
The objective of this research is to find out the maximum production of bread and brownies that must be provided by âSyariah Bakeryâ home industry in order to obtain the maximum profit by optimalizing limited sources. The research was conducted at âSyariah Bakeryâ home industry in Tanamodindi regency, Palu Selatan subdistrict, Palu City in February until April 2015. It had four respondents which consisted of the owner and three employees ofÂ  âSyariah Bakeryâ home industry. In addition, the result of the research showed that the optimal production ofÂ  the home industry by producing 52, 550Â  packages of bread, 1, 218 packages of brownies in every month and by optimalizing 1,729 kg of wheat flour, 278,79 kg of chocolate powder, 403 kg of sugar, and 910 HOK, the maximum profit obtained was Rp. 36,736,050